1992
DOI: 10.1111/j.1365-4362.1992.tb03550.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrotrichogenesis: Further Evidence of Efficacy and Safety on Extended Use

Abstract: These data represent a subset of data from the original 36-week study conducted by Maddin et al., which was in itself a preliminary study of a pulsed electrical stimulation device in male subjects alone. The extension phase of this study, which is summarized here, was undertaken to gather data on longer-term efficacy and safety and to study clinical effects in control subjects who were then switched to active treatment. Thirteen subjects had active treatment for 70 weeks, and 14 subjects were included in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 2 publications
2
13
0
Order By: Relevance
“…In addition, compared to the reported electrical stimulation and MNX approaches for clinical hair regeneration, our m -ESD demonstrated more rapid and generally more effective hair proliferation with a much shorter treatment time (Figure 4f). 16,18,19,4143 This analysis confirmed that the self-generated electric pulses from m -ESD could significantly promote hair regeneration and HF proliferation in SD rats.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…In addition, compared to the reported electrical stimulation and MNX approaches for clinical hair regeneration, our m -ESD demonstrated more rapid and generally more effective hair proliferation with a much shorter treatment time (Figure 4f). 16,18,19,4143 This analysis confirmed that the self-generated electric pulses from m -ESD could significantly promote hair regeneration and HF proliferation in SD rats.…”
Section: Resultssupporting
confidence: 64%
“…Currently, several promising nonpharmacological treatments such as thermal, laser, and electrical stimulation have been developed and are gradually moving into clinical investigation/practice. , Among them, electric stimulation can induce a non-invasive biological effect named electrotrichogenesis (ETG). Though the optimal ETG parameters have not been clinically confirmed, alternating electric field (EF) in the range of 0.1–10 V/cm and frequencies of <15 Hz are commonly used, which imposes negligible tissue damage. , ETG could enhance the influx of calcium ions into the dermal papilla cells via voltage-gated transmembrane ion channels, facilitate ATP synthesis in mitochondria, activate protein kinases, and stimulate protein synthesis and cell division. ,, As a result, the ETG effect is believed to be able to regulate secretion of multiple hair growth factors, promote HF proliferation, prolong the anagen stage, and ultimately promote hair regeneration. ,, Although state-of-the-art extracorporeal treatment apparatuses have miniaturized their sizes to accommodate themselves to wearable devices, the entire system remains bulky and inconvenient for daily treatment as restricted by battery capacity and output current. …”
mentioning
confidence: 99%
“…Besides the pharmacologic therapeutic options mentioned before, there is a wide range of molecules, products and interventions claiming to promote hair growth in AGA. These include cosmetic to pharmaceutical agents, natural products, functional food and even electrostatic/‐magnetic treatment . The mode of application comprises topical application, oral intake and scalp injections.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Four trials for pulsed electrostatic field could be included into the evidence‐based evaluation of the guideline [98–101]. Though the trials showed modest increase in total, anagen or nonvellus hair counts, the use in clinical routine is doubtful due to unfavourable cost‐benefit ratio.…”
Section: Therapeutic Options and Therapy Assessmentmentioning
confidence: 99%